REVIEW OF ACADEMIC LIBRARY INFORMATION AND HUMAN RESOURCES: EVIDENCE FROM OSUN STATE UNIVERSITY, NIGERIA - Gbotosho, Ajibola S.; AJIBOLA, Kolawole Sunday (Annals of Spiru Haret University. Economic Series, 2021)
Generally, the library is referred to as the knowledge hub of higher education institutions, saddled with the responsibility of supporting the teaching, research, and community engagement function in the university. These libraries are conceived to enable them genuinely handle the information needs of library clientele. In the wake of the COVID-19 pandemic, the human traffic to the physical library shrinks which brings more responsibility to the library personnel who works from home to make the library resources available to users at their various locations. The emerging responsibility motivated this study which investigated the appraisal of academic library information resources and human resources in Sola Akinrinade Central Library of Osun State University in Nigeria. A structured questionnaire was used for data collection. A sample of three hundred and forty-five respondents were selected using a simple random sampling technique. Two hundred and seventy-five copies were returned. Findings from the study revealed that available information resources and human resources in the academic library do not meet the accredited academic library standards. Similarly, the academic library is not sufficiently and adequately funded which has grossly affected the provision of the available information and human resources. The researchers recommend that recruitment of professional librarians and other library support staff; provision of quantity and quality information resources, and integration of academic library in the plan of higher institutions among other measures would improve the relevance of library and human resources in higher institutions of learning.